Handwashing Culture Habituation For Children To Prevent Covid-19 Transmission - Dewi Nurhanifah (Comment: an International Journal of Community Development, 2021)
One of the most effective ways to keep our bodies clean is to wash our hands. There are so many benefits of handwashing, it's a shame if you have to ignore it. The World Health Organization (WHO) or the World Health Organization states that our hands are the main route for disease germs to enter the body, therefore the habit of washing hands with soap will reduce and prevent disease. The activity of providing education on how to wash hands properly and correctly is carried out to children because children are a group of people who are still very curious and it is important to be taught from an early age in order to foster a sense of care for personal hygiene and health. The material provided refers to the recommendations of the World Health Organization or the World Health Organization which basically consists of 6 main steps and then additional material is given to complete the handwashing steps. The results obtained were an increase in the understanding of the children there as evidenced by their independence in washing their hands